KAJIAN SEMIOTIKA PIKTOGRAM PADA PENUNJUK ARAH (WAYFINDING) DI JAKARTA - Wahyu Arnisa; Sapta Rika Suprihatin; Wiliayu (Universitas Budi Luhur, 2024)
The implementation of integrated transportation or Jaklingko resulted in the need for Wayfinding Information System Guidelines in Jakarta which were ratified as Gubernatorial Decree No. 31 of 2022 to make it easier for people to mobilize using public transportation. One of the important parts in Wayfinding is pictograms. Based on the survey conducted, there are several pictograms that can be interpreted the same or not as the Gubernatorial Decree. So it is necessary to know how the Wayfinding pictogram process can build meaning and relate to the surrounding community. To answer this, research was carried out with a qualitative approach by conducting surveys and interviews with 29 respondents and continued by carrying out Charles Sanders Peirce's semiotic analysis on the selected pictograms including the five pictograms with the most correct answers, and the five pictograms with the least number of correct meanings. in the Governor's Decree. From the results of this analysis, it is known that pictograms can be interpreted the same way according to the Gubernatorial Decree because they have a form that is familiar to society, while pictograms will be interpreted differently if they are rarely encountered in society. Pictograms are related to the surrounding community, seen from how people interpret the pictograms based on their experience, environment and culture. In order to have the same meaning, the pictogram must come from things that are generally known in society.